Kajian Komparasi Profil Pendidikan Kewarganegaran Sekolah Dasar Di Singapura Dan Indonesia - Muhammad Amin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
Abstract: The purpose of the study is to describe the profile of primary school citizenship education in Singapore and Indonesia. This study is literature research. The primary data of this study is a document of the primary school-level citizenship education curriculum that applies in Singapore and Indonesia, while secondary data is another source of literature that fits the focus of this study. The research data is collected through documentation techniques, then analyzed by content analysis method. The findings of this study are programmatically citizenship education of elementary schools in Singapore and Indonesia included in the separated approach and used as a core program of compulsory subjects and has its own uniqueness.